ECSPECT prospective multicentre registry for single‐port laparoscopic colorectal procedures. Issue 1 (20th October 2016) - Weiss, H.; Zorron, R.; Vestweber, K.‐H.; Vestweber, B.; Boni, L.; Brunner, W.; Sietses, C.; Morales Conde, S.; Bulut, O.; Gash, K.; Dixon, A. R.; Mittermair, C.; et al.
Abstract : Background: The international multicentre registry ECSPECT (European Consensus of Single Port Expertise in Colorectal Treatment) was established to evaluate the general feasibility and safety of single‐port colorectal surgery with regard to preoperative risk assessment. Methods: Consecutive patients undergoing single‐port colorectal surgery were enrolled from 11 European centres between March 2010 and March 2014. Data were analysed to assess patient‐, technique‐ and procedure‐dependent parameters. A validated sex‐adjusted risk chart was developed for prediction of single‐port colorectal surgery‐related conversion and complications. Results: Some 1769 patients were enrolled, 937 with benign and 832 with malignant conditions. Procedures were completed without additional trocars in 1628 patients (92·0 per cent). Conversion to open surgery was required in 75 patients (4·2 per cent) and was related to male sex and ASA fitness grade exceeding I. Conversions were more frequent in pelvic procedures involving the rectum compared with abdominal procedures (8·1 versus 3·2 per cent; odds ratio 2·69, P < 0·001). Postoperative complications were observed in a total of 224 patients (12·7 per cent). Independent predictors of complications included male sex ( P < 0·001), higher ASA grade ( P = 0·006) and rectal procedures ( P = 0·002). The overall 30‐day mortality rate was 0·5 per cent (8 of 1769 patients); three deaths (0·2 per cent; 1 blood loss, 2 leaks) were attributable to surgical causes. Conclusion: The feasibility and safety, conversion and complication profile demonstrated here provides guidance for patient selection. Abstract : Possible but similar to multiport results